2010
DOI: 10.2355/isijinternational.50.1763
|View full text |Cite
|
Sign up to set email alerts
|

A First Attempt to Implement a Swirl Blade in Production of Ingots

Abstract: Fig. 12.Predicted radial steel velocity at the surface at different steel heights during the mold filling. Data are given for the reference case and the three cases with swirl blade at 250, 500 and 750 mm distance to the inlet, for the velocity of 1 m/s. The radial velocity for the flared inlet is also shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 12 publications
0
38
0
Order By: Relevance
“…20) The definition of the hump height (H h ) and the surface height (H s ) for the present model have been discussed in the authors' previous work.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…20) The definition of the hump height (H h ) and the surface height (H s ) for the present model have been discussed in the authors' previous work.…”
Section: Resultsmentioning
confidence: 99%
“…12,13,19,20) In the present study, swirl blades with different orientations in the vertical runner were introduced by considering the mass flow distribution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that a quite stable outlet-flow pattern of the immersion nozzle can be obtained with a swirling flow nozzle 10) and that the penetration depth of the nozzle outlet flow is remarkably decreased in mold. 8) Industrial experimental results 22,23,30) show that the swirling flow SEN effectively improved the steel product quality. In addition, the clogging problem of the SEN outlet port is effectively reduced.…”
Section: Introductionmentioning
confidence: 97%